Synadelph-ureterostomy: Regarding 3 observations - Clark, Omar G.; Fernández Gómez, Washington; Tenca, César; Herrera, Eduardo; Gómez Fynn, Eduardo (Cirugía del Uruguay, 1979)
The paper anaiyzes 3 cases of synadelpho - ureterostomy which we believe to be the first mentioned in national literature. There is a brief review of concept, indications and classification as well as considerations on technique employed; the authors stress the fact that it is easy to petfbrm and morbi-mortality is low.